A blockchain-based anonymous reporting system with no central authority: Architecture and protocol - Saeed Banaeian Far; Maryam Rajabzadeh Asaar (Cyber Security and Applications)
Blockchain technology has emerged as a compelling field of study over the past decade. Nevertheless, certain blockchain-based protocols, particularly those reliant on permissioned blockchains, continue to be under the governance of a central authority (CA). This central authority possesses extensive control capabilities, including the facilitation of user network access, as well as the establishment, connection, and revocation of users to and from the network. Consequently, the majority of policies within these protocols are centrally administered by a singular party. This paper introduces an architectural framework and a specific protocol denoted as the “Anonymous Reporting System with No Central Authority” (ARSnCA) on a public blockchain infrastructure. This design aims to mitigate the challenges posed by untrusted privileged insiders to the ARSnCA. It is hypothesized that this approach can enhance system reliability, fault tolerance, and foster trust among network members. To eliminate the central authority, a concept termed the virtual blockchain (VBC) is implemented as an embedded permissioned blockchain within a permissionless blockchain. Following the removal of the CA, the authorities previously held by the central authority are transferred to the members of the VBC. Comparative analysis and evaluation of the ARSnCA protocol demonstrate a performance advantage, with speeds that are 62% and 92% faster than reporting protocols based on ring signatures and other protocols included in the comparison.